Ten‐year review of gastrointestinal stromal tumours at a tertiary referral hospital in New Zealand. Issue 3 (11th December 2013) - Siu, Joey; Lim, Michael; Fischer, Jesse; Dobbs, Bruce; Wakeman, Chris; Ing, Andrew; Frizelle, Frank
Abstract: Background: Gastrointestinal stromal tumours (GISTs) are the most common mesenchymal tumours of the gastrointestinal tract and make up 1–2% of all gastrointestinal malignancies. Traditionally, the treatment of choice for primary disease is surgical resection; however, no single surgeon or institution gets extensive exposure to these patients so appropriate decision‐making is difficult, particularly since the introduction of the tyrosine kinase inhibitor imatinib, which has become an important additional management tool. Method: All patients were diagnosed and treated for GISTs in Christchurch Hospital (Christchurch, New Zealand) between 1 January 2000 and 31 December 2010. We maintain a prospective database of all patients with GISTs. Data on clinical and histopathological variables, management and survival outcomes were recorded. These were then reviewed. Results: There were 93 patients in this study. Fifty were women. Median age was 69 (interquartile range (IQR) 59–76) years. Fifty‐one tumours were located in the stomach, 27 in the small bowel, six in the colon, three in the oesophagus, one in the rectum and five were extra‐gastrointestinal. In total, 22 patients received imatinib therapy; four patients with metastatic disease had imatinib as sole therapy. The median follow‐up was 58 (IQR 30–90) months. The 5‐year overall survival and disease‐free survival (DFS) for the entire study population was 69% and 64%, respectively. The 5‐year DFS was higher for all patients who have localized disease when compared with those who have metastatic disease (76% versus 28%, P ‐value 0.001). Conclusion: Surgery aiming at an R0 resection remains the mainstay of treatment. We propose the most effective way to grow the knowledge base in New Zealand is the establishment of a national register, thereby allowing better clinical decision‐making by interpretation of a larger data set.